An ecoGothic reading of Hawthorne's 'Young Goodman Brown' and 'Roger Malvin's Burial'. Issue 12 (2nd December 2021) - Talebpour Sheshvan, Narmin; Ghaderi, Farah
ABSTRACT: This article offers an ecoGothic reading of Hawthorne's 'Young Goodman Brown' (1835) and 'Roger Malvin's Burial' (1832). It fleshes out human-nature encounters in the selected short stories to revisit the common response to nature in Hawthorne scholarship as a passive element reflecting characters' state of mind. We argue that the wilderness in both short stories is presented as a malevolent and dystopian space which is actively resistant and hostile to human intrusion. We explore the ways that nature reacts to intruders in both stories drawing on the main concepts of ecoGothic criticism. The article indicates that descriptions of the wilderness in these stories are framed in Gothic terms; nature appears as disturbed and disturbing, haunted and haunting. The gloomy wilderness of the stories generates fear in the intruders not only by its uncharted space and bewildering structure but also through the possibility of the menacing presence of the Indians. Nature in the selected stories overpowers humans, punishes them severely and reclaims its space at the end.